Levodopa in Parkinsonism: reduction in the electromyographic silent period and its relationship with tremor - McLellan, D. L. (1972)
The electromyographic silent period after electrical stimulation of the median nerve was recorded by surface electrodes over the abductor pollicis brevis muscle in 32 patients with Parkinsonism before and after treatment with levodopa. A supra-maximal stimulus was delivered during maximal isometric contraction of the muscle. The silent period was prolonged in the untreated state compared with controls, but shortened significantly as a result of treatment. Observation of the clinical effects of treatment in each patient showed a relationship between shortening of the silent period and improvement in resting tremor. There was no relationship between the duration of the silent period and rigidity. The significance of these findings is discussed. They are considered to support the view that inhibition of motoneurone activity by afferent stimuli is intensified in Parkinsonism and that there is a close relationship between the degree of motoneurone inhibition and the severity of tremor.